Reading and Understanding Financial Reports in the Sudan:Extent and Difficulties - D., Saadaby M.; H., Mohamed El-Amin T. (Gezira Journal of Economic and Social Sciences, 2015)
There are many factors that are having an adverse effect on the readability and comprehension of financial reports in the Sudan. Therefore, this study aimed mainly to explore and assess the ability of financial reports in the Sudan to accomplish the goal of providing information to the users in a readable and understandable manner. The tool used to collect the data was the questionnaire which has been distributed to a sample of 175 users of financial reports and 21auditors. To analyze the data, the study depended on a variety of methods including percentage frequencies, skewness, measures of central tendency, standard deviation, and the minimum and maximum values. In addition, Chi-square (X2) and Mann Whitney U test were also used as appropriate techniques to test the difference in perceptions between both users and auditors. The most important results the study ended up with were that; the users in the Sudan were faced by either a high or a moderate level of difficulty in reading financial reports when they deal with such report. Such readers, however, attached a high importance to the reading of such reports. This high level of difficulty in reading was attributed to the complexity and difficulty of the language used in preparing the financial reports, weakness of the users' ability to read and understand them, in addition to the use of vague and unclear terms which lead to confusion and misunderstanding. Another finding is that the “not understanding” and “inappropriateness to decision- making” of some reports were attributed to some problems related to the characteristics and amount of information in the reports themselves and, the language and format of these reports, in addition to the weak ability of the users to understand such reports. The study recommended that the professional bodies of accounting and educational institutions  should reconsider the language used to prepare the financial reports in the Sudan and the format adopted to review their contents of information, in addition to reconsidering the amount of information involved in such reports.